Hidden mechanical weaknesses within lava domes provided by buried high‑porosity hydrothermal alteration zones - Darmawan, Herlan (Nature Research, 2022)
Catastrophic lava dome collapse is considered an unpredictable volcanic hazard because the physical properties, stress conditions, and internal structure of lava domes are not well understood and can change rapidly through time. To explain the locations of dome instabilities at Merapi volcano, Indonesia, we combined geochemical and mineralogical analyses, rock physical property measurements, drone-based photogrammetry, and geoinformatics. We show that a horseshoe-shaped alteration zone that formed in 2014 was subsequently buried by renewed lava extrusion in 2018. Drone data, as well as geomechanical, mineralogical, and oxygen isotope data suggest that this zone is characterized by high-porosity hydrothermally altered materials that are mechanically weak. We additionally show that the new lava dome is currently collapsing along this now-hidden weak alteration zone, highlighting that a detailed understanding of dome architecture, made possible using the monitoring techniques employed here, is essential for assessing hazards associated with dome and edifice failure at volcanoes worldwide.